Awareness of prostate cancer and its associated factors among men 40 years of age and older in Mizan Aman town, Bench Sheko zone, Southern Nations, Nationalities, and Peoples’ Region, South West Ethiopia, 2019 - Assefa, Ashenafi; Germossa, Gugsa Nemera; Ayenew, Mengistu; Bedada, Gadisa Bekele (Frontiers in Oncology, 2022)
Background Prostate cancer is a common cause of morbidity and mortality among men aged 40 years and older. Evidence has shown that awareness of prostate cancer plays a greater role in the early detection of prostate cancer. However, there is a paucity of information regarding prostate cancer awareness levels in Ethiopia in general and in Mizan Aman town in particular. Objectives To assess the awareness of prostate cancer and its associated factors among men aged 40 years and older in Mizan Aman, Bench Sheko zone, Southern Nations, Nationalities, and Peoples’ Region, South West Ethiopia, 2019. Methods A community-based cross-sectional study was conducted from 1 to 30 April 2021 in Mizan Aman town. A total of 322 study subjects were selected from a total population of 1,242 in Mizan Aman town by using the simple random sampling method. Data were collected through a face-to-face interview using a structured questionnaire. Data were entered into EpiData version 3.1 and analyzed by Statistical Package for Social Science version 20. Descriptive statistics were used to summarize sociodemographic characteristics and personal history. Bivariate and multivariate regression analyses were used to explore further variables that were associated with the level of awareness. Significant associations were declared at a p-value of <0.05. The results were presented in text, tables, and charts. Results The magnitude of prostate cancer awareness was 64%. Participants who were between 40 and 55 years of age (adjusted odd ratio = 6.16, 95% confidence interval = 2.62–14.47), who were government employees (adjusted odd ratio = 4.684, 95% confidence interval = 1.56–13.97), and whose monthly income level is greater than 5,000 birr (adjusted odd ratio = 12.45, 95% confidence interval = 3.2–47.77) were significantly associated with the level of awareness. Conclusion and recommendation This study revealed that more than half of the men residing in Mizan Aman town had a high level of prostate cancer awareness. First-category age, better economic status, and employment were significantly associated with awareness of prostate cancer. This indicates the need for a collective effort to enhance the awareness of men regarding prostate cancer.